Introducing a nursing maintenance bundle for patients with pulmonary arterial catheters. (21st October 2019) - Ben-Aderet, Michael A.; Almario, Matthew J. P.; Madhusudhan, Meghan S.; Drucker, Carissa; Luria, Jeffery; Krishna, Sneha; Massie, Laila; Bresee, Catherine; Chan, Alice; Nguyen, Jimmy; Murthy, Rekha K.; Grein, Jonathan D.
Abstract: We undertook a quality improvement project to address challenges with pulmonary artery catheter (PAC) line maintenance in a setting of low-baseline central-line infection rates. We observed a subsequent reduction in Staphylococcal PAC line infections and a trend toward a reduction in overall PAC infection rates over 1 year.